FINANCIAL INCLUSION AND CO2 EMISSIONS IN ASIA: IMPLICATIONS FOR ENVIRONMENTAL SUSTAINABILITY - Asengbaramae, Rowiyah (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Financial inclusion and CO2 emissions are two important factors in the context of environmental sustainability in Asia. Financial inclusion, which refers to public access and participation in formal financial services, can impact the ability of individuals and communities to invest in environmentally friendly technologies and sustainable business practices. On the other hand, CO2 emissions, the relationship between financial inclusion and CO2 emission levels in Asia, as well as their implications for environmental sustainability. This paper explores how increased access to financial services can affect the reduction of CO2 emissions, both through changes in consumer behavior and innovation in the industrial sector. To achieve better environmental sustainability, it is important for policymakers and stakeholders to consider the synergies between the financial and environmental sectors, as well as design strategies that support the transition to a greener and more inclusive economy.